Targeting cytokine and chemokine signaling pathways for cancer therapy - Ming Yi; Tianye Li; Mengke Niu; Haoxiang Zhang; Yuze Wu; Kongming Wu; Zhijun Dai (Signal Transduction and Targeted Therapy, 2024)
Abstract Cytokines are critical in regulating immune responses and cellular behavior, playing dual roles in both normal physiology and the pathology of diseases such as cancer. These molecules, including interleukins, interferons, tumor necrosis factors, chemokines, and growth factors like TGF-β, VEGF, and EGF, can promote or inhibit tumor growth, influence the tumor microenvironment, and impact the efficacy of cancer treatments. Recent advances in targeting these pathways have shown promising therapeutic potential, offering new strategies to modulate the immune system, inhibit tumor progression, and overcome resistance to conventional therapies. In this review, we summarized the current understanding and therapeutic implications of targeting cytokine and chemokine signaling pathways in cancer. By exploring the roles of these molecules in tumor biology and the immune response, we highlighted the development of novel therapeutic agents aimed at modulating these pathways to combat cancer. The review elaborated on the dual nature of cytokines as both promoters and suppressors of tumorigenesis, depending on the context, and discussed the challenges and opportunities this presents for therapeutic intervention. We also examined the latest advancements in targeted therapies, including monoclonal antibodies, bispecific antibodies, receptor inhibitors, fusion proteins, engineered cytokine variants, and their impact on tumor growth, metastasis, and the tumor microenvironment. Additionally, we evaluated the potential of combining these targeted therapies with other treatment modalities to overcome resistance and improve patient outcomes. Besides, we also focused on the ongoing research and clinical trials that are pivotal in advancing our understanding and application of cytokine- and chemokine-targeted therapies for cancer patients.